2019
DOI: 10.1523/jneurosci.3415-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin-Dependent Mitophagy Guides Outcome after Traumatic Brain Injury

Abstract: Mitochondrial energy production is essential for normal brain function. Traumatic brain injury (TBI) increases brain energy demands, results in the activation of mitochondrial respiration, associated with enhanced generation of reactive oxygen species. This chain of events triggers neuronal apoptosis via oxidation of a mitochondria-specific phospholipid, cardiolipin (CL). One pathway through which cells can avoid apoptosis is via elimination of damaged mitochondria by mitophagy. Previously, we showed that exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 58 publications
1
66
0
Order By: Relevance
“…While cardiolipin, a phospholipid mainly localized at the inner mitochondrial membrane, can externalize to the outer membrane and serve as a mitophagy receptor in neuronal cells (Chu et al, 2013). Cardiolipin mediated mitophagy has been shown to play an important role in traumatic brain injury (TBI) by removing damaged mitochondria thus mitigating ROS overproduction and decreasing apoptosis (Chao et al, 2019).…”
Section: Other Mitophagy Receptorsmentioning
confidence: 99%
“…While cardiolipin, a phospholipid mainly localized at the inner mitochondrial membrane, can externalize to the outer membrane and serve as a mitophagy receptor in neuronal cells (Chu et al, 2013). Cardiolipin mediated mitophagy has been shown to play an important role in traumatic brain injury (TBI) by removing damaged mitochondria thus mitigating ROS overproduction and decreasing apoptosis (Chao et al, 2019).…”
Section: Other Mitophagy Receptorsmentioning
confidence: 99%
“…Mitochondria are indispensable organelles for energy production, cell signaling, and cell survival in eukaryotic cells. However, damaged and dysfunctional mitochondria are also responsible for generating the majority of reactive oxygen species (ROS) and the release of cytochrome c (cyt c), which results in cell death 12 . Thus selective elimination of damaged mitochondria by mitophagy could be a potential therapeutic target for TBI.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of CL externalization as a signal to degrade damaged mitochondria via autophagy has been demonstrated in vitro and in vivo [16,18,22,31]. In this work, LC3A has been identified as an additional LC3 family member involved in mitophagy, and key residues for its interaction with CL have been singled out.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have demonstrated that CL-externalization takes place also in vivo. Traumatic Brain Injury (TBI) model animals externalize CL to the OMM to a similar extent than rotenone-exposed mitochondria, thus underlining the importance of CL for mitophagy induction during the early response to this injury in human and rat brain [18]. Moreover, it is known that taffazin-deficiency related perturbations in CL remodeling related to Barth syndrome cause defective mitophagosome biogenesis [19].…”
Section: Introductionmentioning
confidence: 99%